Hubungan parameter kualitas air dengan kelimpahan fitoplankton pada budidaya udang vannamei pola intensif di Situbondo Jawa Timur - Shania Maulidhya; Husain Latuconsina; Hamdani Dwi Prasetya (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2025)
Optimal shrimp growth and harvest are greatly influenced by water quality as the dominant factor in influencing shrimp growth and survival. The aim of this research is to analyze the relationship between water quality and phytoplankton abundance. This research uses a survey method. Determination of stations and sampling points using the purposive sampling method. The composition of phytoplankton found in the waters of vaname shrimp ponds consists of 5 classes with a total of 9 genera, while when it is sunny the number is greater (12 genera). Bacillariophyceae dominate waters when it rains while Chlorophyceae dominate waters when it is sunny. The percentage composition of plankton species was as expected except for the Cyanophyceae group when it was sunny. The genus Rhizosolenia was found which is thought to be an indicator of eutrophication. The average value reported for phytoplankton from the three sampling stations during rain ranges between 3.06x106 - 5.48x106 ind/L. Not much different, the bright times obtained ranged from 4.03x106 - 6.61x106 ind/l. Abundance at all sampling points indicates eutrophic waters (>15000). Air quality in general is no different and meets quality standards except for nitrate and phosphate values. The temperature and brightness parameters have the highest level of relationship with plankton delivery compared to other parameters. The quality of coastal waters is positive except for pH and nitrate. The PCA results showed that there were differences in abundance between observation stations and between rainy and sunny conditions.